Customers' Expectations and Satisfaction with Online Food Ordering Portals - Bagla, Ramesh Kumar; Khan, Jasmine (Prabandhan: Indian Journal of Management, 2017)
Purpose : This paper investigated the factors that are responsible for the growing popularity of online booking and ordering of food in India, expectations of the users, and their satisfaction levels with the popular apps such as Foodpanda, Swiggy, and Zomato. Methodology : Descriptive research was undertaken on the basis of primary data collected from the respondents residing in National Capital Region of Delhi chosen through non – probability convenience sampling using a structured questionnaire. The collected data were converted into data matrix using SPSS 23.0 software and inferential analysis was done. Findings : Factors contributing to the popularity of online food ordering were found to be : lack of time to prepare food, availability of variety, rewards and cashbacks. There is a scope for improving the users' satisfaction levels by understanding their expectations more precisely and offering more attractive options while ordering food online. Research Limitations/Implications : The study was limited to a specified geographical area of National Capital Region of Delhi for chosen factors considered by customers while ordering food online conducted at a particular stage of evolution of the online food industry. Originality/Value : The paper offered fresh insights into customers' expectations and the relative importance of the factors considered by them while ordering food online. The findings of this research can be used by online food portals for bridging the gaps between customer expectations and their satisfaction level to ensure sustainability of this innovation.